SISTEM INFORMASI GEOGRAFIS PEMETAAN BENCANA ALAM DI PROVINSI SULAWESI TENGAH - Sri Khaerawati Nur; Sukardi; Kevin Maitano (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Natural disaster is an event related to natural phenomena that causes damage to a location on a small to large scale. According to data from the National Disaster Management Agency (BNPB), the number of disasters that occurred in Central Sulawesi in 2016–2020 totaled 251 cases. Determining the location of natural disasters will be one of the factors to facilitate government access in solving problems. Until now, the government does not have a Geographic Information System (GIS) in the form of mapping the location points of natural disasters that have occurred. Based on the problems above, a website-based information system was created, namely